Clinicopathologic study and Ki-67 proliferative marker evaluation in human osteosarcomas - Marinho, Larissa Cardoso (2005)
BACKGROUND: Osteosarcoma is a relatively uncommon malignant neoplasm and little information has been reported on its cell proliferation using Ki-67. OBJECTIVES: Evaluate histological, clinical and immunohistochemical parameters using Ki-67 labeling index (LI), correlate one to another and with follow-up. MATERIAL AND METHOD: Fifty-seven patients with available clinicopathological data submitted to the study of cell proliferation as determined by Ki-67 expression measured by immunohistochemistry (IHC) staining using formalin-fixed paraffin embedded sections. In each sample, positive cells were quantified on at least a thousand nuclei and expressed as Ki-67 LI according to median value. RESULTS AND DISCUSSION: Non-significant correlations were observed in metastatic and non-metastatic cases when variables as surgery, tumor size, death and relapse were compared with Ki-67 LI values (cut-off of 45%). In the group of non-metastatic cases there was a direct correlation between higher values of Ki-67 index and better overall survival. Metastatic patients overall survival curve and LI high and low Ki-67 did not show significant differences. CONCLUSION: Based on our results the Ki-67 LI could be useful as a prognostic marker in patients without metastasis at diagnosis.